Analisa Perbaikan Sistem Kerja Menggunakan Metode RULA dan REBA di Pabrik Tahu Sumedang ABC - Khoirunnisa, Siti; Yetty Meuthia Hasibuan; Abdul Azis Syarif (SURYA TEKNIKA, 2024)
Health problems related to an operator's posture while working can have a major impact on productivity and efficiency levels. To minimize the possibility of disturbances in posture and injury to operators, improvements are made to work methods, adjustments to machines or work aids, rearrangement of machine positions, and changes to work movements in accordance with suggestions from the RULA analysis. At ABC's Sumedang Tofu Factory, which consists of six work stations (washing, converting, pressing, grinding, molding, and packaging), ergonomic analysis indicated that incorrect working postures could cause discomfort and fatigue in the upper body of workers. After making improvements to the working posture, the final RULA value for the milling section was reduced from 7 to 2, and for the packing section from 5 to 3, indicating that the risk had decreased to an acceptable level. The REBA method also shows a decrease in scores in the milling section from 8 to 2, and in the packing section from 5 to 3, which indicates an improvement in working posture which is better and more acceptable